Waterproof down feather manufacturing method
By cross-linking and hydrophobic modification of down velvet, the problem of increasing hydrophilicity of down velvet after washing is solved, the warming performance and resistance to water are improved, and the service life is extended.
Patent Information
- Application Number
- CN202411557417.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
AI Technical Summary
After washing and processing of existing down products, the hydrophilicity of the velvet increases, resulting in poor warming effect and is not suitable for dry cleaning. Machine-washing and washing will also cause velvet damage.
The down sliver is obtained by immersing the down sliver in sequentially into a mixed solution of oxalic acid solution and a mixed solution of oligomal maleic acid and sodium hypophosphate, and then undergoing surface hydrophobic modification.
It improves the correlation between velvets and resistance to air, enhances the warmth performance, and improves the resistance to water through hydrophobic modification, and extends the service life.
Smart Images

Figure BDA0005116901690000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of down, and in particular relates to a method for making waterproof down. Background Art
[0002] The new national standard replaces the original "down content" regulation that calculates down and down silk together with a separate "down content", indicating that the single down silk that falls off from the root of down or feather pieces is no longer counted. Unlike down, which can be filled with air between dense branches to produce a warming effect, individual down silk cannot be effectively gathered; and the internal protein peptide chain structure exposed by the break and the destruction of the surface hydrophobic layer caused by the washing process will increase the hydrophilicity of the down silk, which is easy to gather water but not easy to discharge. These factors make the warmth-keeping effect of the down silk poor. With the existing down washing processing technology, due to its own quality and processing loss, after processing, the content of down silk and feather silk with higher quality and higher maturity is generally within 7%; the ordinary down purchased on the market and the duck down with a short breeding cycle generally have a down silk and feather silk content close to 10%. Therefore, a large amount of down silk will be produced after each down product processing. If these down silks that have undergone the washing process are directly discarded, it will be a great waste.
[0003] In terms of chemical properties, down is acid-resistant but not alkali-resistant. Alkali has a strong effect on down and has a great destructive effect on it. Generally speaking, weak alkaline solutions will damage down. When the pH is ≥10, the down will be severely damaged. However, because the chemicals used for dry cleaning will destroy the structure of down, down products are not suitable for dry cleaning, and machine washing and water washing processes will also cause damage to the down and reduce its warmth retention. In order to minimize the damage to down after washing, the damage to down can be reduced by improving the waterproofness of down. Summary of the invention
[0004] The present invention mainly provides a kind of down that can be gathered together and has high fluffiness and is waterproof. The technical scheme is as follows:
[0005] A method for making waterproof down comprises the following steps: immersing down fibers in an oxalic acid solution and a mixed solution of oligomeric maleic acid and sodium hypophosphite in turn, and then cross-linking to obtain cross-linked down fibers; and performing surface hydrophobic modification on the cross-linked down fibers to obtain waterproof down.
[0006] Further, the following steps are included:
[0007] a. Dissolve oxalic acid in water to obtain an oxalic acid solution; take clean down silk and immerse it in the oxalic acid solution, take out the down silk after homogenization, and dry it in a vacuum at 60-80℃ for 1-3h to obtain moist down silk containing oxalic acid;
[0008] b. dissolving oligomeric maleic acid and sodium hypophosphite in water to obtain a mixed solution of oligomeric maleic acid; immersing the oxalic acid-containing velvet in the oligomeric maleic acid solution, and after sufficient homogenization, taking out the velvet and cross-linking it to obtain a cross-linked velvet;
[0009] c. Then keep the temperature at 100-80°C, spray the octadecyl isocyanate solution on the cross-linked down fibers until the cross-linked down fibers are fully soaked, control the temperature at 55-70°C and keep it for 1.5-3 hours, and dry it at low temperature to obtain waterproof down.
[0010] Furthermore, the concentration of the oxalic acid solution in step a is 20 to 30 g / L.
[0011] Furthermore, the remaining rates of the velvet in step a and the velvet containing oxalic acid in step b after immersion and removal are both 75-85%.
[0012] Furthermore, in the oligomeric maleic acid mixed solution of step b, the concentration of the oligomeric maleic acid is 70-90 g / L, and the concentration of the sodium hypophosphite is 40-60 g / L.
[0013] Furthermore, the cross-linking step in step b is as follows: vacuum drying the taken out velvet yarn at 60-80° C. for 0.5-2 h, then heating it to 160-190° C. and then reducing the temperature to 100-80° C. at the same speed to obtain cross-linked velvet yarn.
[0014] Furthermore, the heating rate is 3 to 8°C / min.
[0015] Furthermore, the concentration of the octadecyl isocyanate solution in step c is 10 to 20 g / L.
[0016] The waterproof down prepared by the method comprises down fibers which are cross-linked with each other and a hydrophobic modifier covering the down fibers.
[0017] Furthermore, the surface contact angle is greater than 120°.
[0018] By adopting the above scheme, the method of the present invention has the following advantages:
[0019] 1. The present invention polymerizes the down fibers to improve the correlation between the down fibers and increase the resistance to air, thereby improving the thermal insulation performance. The invention also performs hydrophobic modification to further improve the connection strength and water resistance of the down fibers, resulting in high fluffiness and strong practicality.
[0020] 2. The present invention utilizes a large number of hydrophilic groups such as amino groups exposed after the velvet fibers are broken, and polymerizes and cross-links with oxalic acid and oligomeric maleic acid to reduce the air flowability between the velvet fibers and improve the fluffiness and warmth retention performance.
[0021] 3. The present invention firstly impregnates the velvet with oxalic acid having a lower molecular weight, so that the subsequent impregnation of the velvet with oligomeric maleic acid having a higher molecular weight is easier and the cross-linking is more complete.
[0022] 4. The present invention directly performs hydrophobic modification after cross-linking to improve the hydrophobic property of the velvet yarn, making the velvet yarn more resistant to water washing, which is beneficial to maintaining the cross-linking strength between the velvet yarns, extending the service life, and preventing moisture from accumulating, thereby providing better warmth retention.
[0023] 5. The production method of the present invention is simple, the equipment requirements are low, the function is close to velvet, and the practicability is strong. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Embodiment 1:
[0026] (1) dissolving oxalic acid in water to obtain a 30 g / L oxalic acid solution; taking clean down fibers and immersing them in the oxalic acid solution, homogenizing and taking out the down fibers so that the remaining rate is 80%; and drying them in a vacuum at 70° C. for 2 h to obtain moist down fibers containing oxalic acid;
[0027] (2) dissolving oligomeric maleic acid and sodium hypophosphite in water to obtain an oligomeric maleic acid mixed solution having a concentration of 90 g / L of oligomeric maleic acid and a concentration of 50 g / L of sodium hypophosphite; immersing oxalic acid-containing velvet in the oligomeric maleic acid solution, and after being fully homogenized, taking out the velvet to make a residual rate of 80%; vacuum drying at 70° C. for 1 hour, and then heating to 180° C. at a rate of 8° C. / min, and then cooling to 90° C. at the same rate to obtain cross-linked velvet;
[0028] (3) Then, the temperature is maintained at 80° C., and 10 g / L octadecyl isocyanate solution is sprayed onto the cross-linked down fibers until the cross-linked down fibers are fully soaked. The temperature is controlled at 60° C. and maintained for 2 h. After low-temperature drying, waterproof down is obtained.
[0029] Embodiment 2:
[0030] (1) dissolving oxalic acid in water to obtain a 30 g / L oxalic acid solution; taking clean down fibers and immersing them in the oxalic acid solution, homogenizing and taking out the down fibers so that the remaining rate is 80%; and drying them in a vacuum at 70° C. for 2 h to obtain moist down fibers containing oxalic acid;
[0031] (2) dissolving oligomeric maleic acid and sodium hypophosphite in water to obtain an oligomeric maleic acid mixed solution having a concentration of 70 g / L of oligomeric maleic acid and a concentration of 50 g / L of sodium hypophosphite; immersing oxalic acid-containing velvet in the oligomeric maleic acid solution, and after being fully homogenized, taking out the velvet to make a residual rate of 80%; vacuum drying at 70° C. for 1 hour, and then heating to 180° C. at a rate of 8° C. / min, and then cooling to 90° C. at the same rate to obtain cross-linked velvet;
[0032] (3) Then, the temperature is maintained at 80° C., and 10 g / L octadecyl isocyanate solution is sprayed onto the cross-linked down fibers until the cross-linked down fibers are fully soaked. The temperature is controlled at 60° C. and maintained for 2 h. After low-temperature drying, waterproof down is obtained.
[0033] Embodiment 3:
[0034] (1) dissolving oxalic acid in water to obtain a 30 g / L oxalic acid solution; taking clean down fibers and immersing them in the oxalic acid solution, homogenizing and taking out the down fibers so that the remaining rate is 80%; and drying them in a vacuum at 70° C. for 2 h to obtain moist down fibers containing oxalic acid;
[0035] (2) dissolving oligomeric maleic acid and sodium hypophosphite in water to obtain an oligomeric maleic acid mixed solution having a concentration of 90 g / L of oligomeric maleic acid and a concentration of 50 g / L of sodium hypophosphite; immersing oxalic acid-containing velvet in the oligomeric maleic acid solution, and after being fully homogenized, taking out the velvet to make a residual rate of 80%; vacuum drying at 70° C. for 1 hour, and then heating to 180° C. at a rate of 3° C. / min, and then cooling to 90° C. at the same rate to obtain cross-linked velvet;
[0036] (3) Then, the temperature is maintained at 80° C., and 10 g / L octadecyl isocyanate solution is sprayed onto the cross-linked down fibers until the cross-linked down fibers are fully soaked. The temperature is controlled at 60° C. and maintained for 2 h. After low-temperature drying, waterproof down is obtained.
[0037] Embodiment 4:
[0038] (1) dissolving oxalic acid in water to obtain a 30 g / L oxalic acid solution; taking clean down fibers and immersing them in the oxalic acid solution, homogenizing and taking out the down fibers so that the remaining rate is 80%; and drying them in a vacuum at 70° C. for 2 h to obtain moist down fibers containing oxalic acid;
[0039] (2) dissolving oligomeric maleic acid and sodium hypophosphite in water to obtain an oligomeric maleic acid mixed solution having a concentration of 90 g / L of oligomeric maleic acid and a concentration of 50 g / L of sodium hypophosphite; immersing oxalic acid-containing velvet in the oligomeric maleic acid solution, and after being fully homogenized, taking out the velvet to make a residual rate of 80%; vacuum drying at 70° C. for 1 hour, and then heating to 180° C. at a rate of 8° C. / min, and then cooling to 90° C. at the same rate to obtain cross-linked velvet;
[0040] (3) Then, the temperature is maintained at 100° C., and a 10 g / L octadecyl isocyanate solution is sprayed onto the cross-linked down fibers until the cross-linked down fibers are fully soaked. The temperature is controlled at 60° C. and maintained for 2 h. After low-temperature drying, waterproof down is obtained.
[0041] Embodiment 5:
[0042] (1) dissolving oxalic acid in water to obtain a 30 g / L oxalic acid solution; taking clean down fibers and immersing them in the oxalic acid solution, homogenizing and taking out the down fibers so that the remaining rate is 80%; and drying them in a vacuum at 70° C. for 2 h to obtain moist down fibers containing oxalic acid;
[0043] (2) dissolving oligomeric maleic acid and sodium hypophosphite in water to obtain an oligomeric maleic acid mixed solution having a concentration of 90 g / L of oligomeric maleic acid and a concentration of 50 g / L of sodium hypophosphite; immersing oxalic acid-containing velvet in the oligomeric maleic acid solution, and after being fully homogenized, taking out the velvet to make a residual rate of 80%; vacuum drying at 70° C. for 1 hour, and then heating to 180° C. at a rate of 8° C. / min, and then cooling to 90° C. at the same rate to obtain cross-linked velvet;
[0044] (3) Then, the temperature is maintained at 80° C., and 20 g / L octadecyl isocyanate solution is sprayed onto the cross-linked down fibers until the cross-linked down fibers are fully soaked. The temperature is controlled at 60° C. and maintained for 2 h. After low-temperature drying, waterproof down is obtained.
[0045] Comparative Example 1:
[0046] (1) dissolving oxalic acid in water to obtain a 30 g / L oxalic acid solution; taking clean down fibers and immersing them in the oxalic acid solution, homogenizing and taking out the down fibers so that the remaining rate is 80%; and drying them in a vacuum at 70° C. for 2 h to obtain moist down fibers containing oxalic acid;
[0047] (2) Dissolve oligomeric maleic acid and sodium hypophosphite in water to obtain a mixed oligomeric maleic acid solution having a concentration of 90 g / L of oligomeric maleic acid and a concentration of 50 g / L of sodium hypophosphite; immerse oxalic acid-containing velvet in the oligomeric maleic acid solution, and after sufficient homogenization, take out the velvet to make the residual rate 80%; vacuum bake at 70°C for 1 hour, and then heat to 180°C at a rate of 8°C / min, and then cool to 90°C at the same rate, take out and dry at low temperature to obtain the product.
[0048] Comparative Example 2:
[0049] 10 g / L octadecyl isocyanate solution was sprayed onto clean down fibers until the fibers were fully soaked, and the fibers were kept at 60° C. for 2 h and dried at low temperature to obtain waterproof down.
[0050] The contact angle of the down products of each embodiment and comparative example with water was tested by the static drop method. The fluffiness of the down products of each embodiment and comparative example was evaluated according to TB / TCFDIA001-2016 "Down Classification Standard".
[0051] The results are as follows:
[0052]
[0053] As can be seen from the above table, Example 1 with a higher maleic acid content has a better fluffiness than Example 2, and compared with the uncrosslinked Comparative Example 2, the fluffiness is significantly increased, reaching the quality of conventional down. When crosslinking, the fluffiness of Example 3 with a slower heating rate is not as good as that of Example 1. It may be that the slow heating rate makes the down fibers treated at high temperature for a longer time, which is easy to destroy the matrix structure of the down fibers. Combining Examples 1 to 3 and Comparative Example 2, it can be seen that crosslinking the down fibers can significantly improve the fluffiness of the down fibers, which has a significant positive effect on improving their thermal insulation capacity. When performing hydrophobic modification, the contact angle of the sample of Example 4 with a higher ambient temperature when spraying the hydrophobic agent is significantly smaller than that of Example 1, and the fluffiness also decreases, indicating that the high temperature at this time is not conducive to the hydrophobic modification. The contact angle of Example 5 with a higher concentration of the modifier increases, but in terms of the degree of increase, the conversion rate is low, and the fluffiness also decreases, indicating that the concentration cannot be increased blindly. Too high a concentration will increase the cost and affect the structure of the product. Comparative Example 1 was not hydrophobically modified, the contact angle of the product was small, and the fluffiness was significantly lower than that of Example 1. Combining Example 4, Example 5 and Comparative Example 1, it can be seen that the hydrophobic modification of the velvet is also beneficial to improving the fluffiness of the product.
[0054] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.
Claims
1. A method for producing waterproof down, characterized in that: The following steps are involved: The down fibers are sequentially immersed in an oxalic acid solution and a mixed solution of oligomeric maleic acid and sodium hypophosphite, and then cross-linked to obtain cross-linked down fibers; The surface of the cross-linked down yarn is hydrophobically modified to obtain waterproof down.
2. The method for making waterproof down according to claim 1, characterized in that: The following steps are involved: a. Dissolve oxalic acid in water to obtain an oxalic acid solution; take clean down silk and immerse it in the oxalic acid solution, take out the down silk after homogenization, and dry it in a vacuum at 60-80℃ for 1-3h to obtain moist down silk containing oxalic acid; b. dissolving oligomeric maleic acid and sodium hypophosphite in water to obtain a mixed solution of oligomeric maleic acid; immersing the oxalic acid-containing velvet in the oligomeric maleic acid solution, and after sufficient homogenization, taking out the velvet and cross-linking it to obtain a cross-linked velvet; c. Then keep the temperature at 100-80°C, spray the octadecyl isocyanate solution on the cross-linked down fibers until the cross-linked down fibers are fully soaked, control the temperature at 55-70°C and keep it for 1.5-3 hours, and dry it at low temperature to obtain waterproof down.
3. The method for making waterproof down according to claim 2, characterized in that: The concentration of the oxalic acid solution in step a is 20-30 g / L.
4. The method for making waterproof down according to claim 2, characterized in that: The remaining rates of the velvet in step a and the velvet containing oxalic acid in step b after being immersed and taken out are both 75-85%.
5. The waterproof down production method according to claim 2, characterized in that: In the oligomeric maleic acid mixed solution of step b, the concentration of the oligomeric maleic acid is 70-90 g / L, and the concentration of the sodium hypophosphite is 40-60 g / L.
6. The method for making waterproof down according to claim 2, characterized in that: The cross-linking step in step b is as follows: vacuum drying the taken-out velvet yarn at 60-80° C. for 0.5-2 h, then heating it to 160-190° C. and then reducing the temperature to 100-80° C. at the same speed to obtain cross-linked velvet yarn.
7. The method for making waterproof down according to claim 6, characterized in that: The heating rate is 3-8°C / min.
8. The method for making waterproof down according to claim 4, characterized in that: The concentration of the octadecyl isocyanate solution in step c is 10-20 g / L.
9. A waterproof down prepared by the method according to any one of claims 1 to 8, characterized in that: The invention comprises down fibers which are cross-linked with each other and a hydrophobic modifier covering the down fibers.
10. The waterproof down according to claim 1, characterized in that: The surface contact angle is greater than 120°.
Citation Information
Cited By
Modification treatment method for improving heat storage property of down feather
CN119932921A
A modification method for improving the heat storage property of down
CN119932921B